Bleeding risk during treatment of acute thrombotic events with subcutaneous LMWH compared to intravenous unfractionated heparin; a systematic review. - Giorgio Costantino; Elisa Ceriani; Anna Maria Rusconi; Gian Marco Podda; Nicola Montano; Piergiorgio Duca; Marco Cattaneo; Giovanni Casazza (PLoS ONE)
Background Low Molecular Weight Heparins (LMWH) are at least as effective antithrombotic drugs as Unfractionated Heparin (UFH). However, it is still unclear whether the safety profiles of LMWH and UFH differ. We performed a systematic review to compare the bleeding risk of fixed dose subcutaneous LMWH and adjusted dose UFH for treatment of venous thromboembolism (VTE) or acute coronary syndromes (ACS). Major bleeding was the primary end point. Methods Electronic databases (MEDLINE, EMBASE, and the Cochrane Library) were searched up to May 2010 with no language restrictions. Randomized controlled trials in which subcutaneous LMWH were compared to intravenous UFH for the treatment of acute thrombotic events were selected. Two reviewers independently screened studies and extracted data on study design, study quality, incidence of major bleeding, patients' characteristics, type, dose and number of daily administrations of LMWH, co-treatments, study end points and efficacy outcome. Pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated using the random effects model. Results Twenty-seven studies were included. A total of 14,002 patients received UFH and 14,635 patients LMWH. Overall, no difference in major bleeding was observed between LMWH patients and UFH (OR = 0.79, 95% CI 0.60-1.04). In patients with VTE LMWH appeared safer than UFH, (OR = 0.68, 95% CI 0.47-1.00). Conclusion The results of our systematic review suggest that the use of LMWH in the treatment of VTE might be associated with a reduction in major bleeding compared with UFH. The choice of which heparin to use to minimize bleeding risk must be based on the single patient, taking into account the bleeding profile of different heparins in different settings.